Sinonasal Imaging Findings in Granulomatosis with Polyangiitis (Wegener Granulomatosis): A Systematic Review. Issue 1 (January 2017) - D'Anza, Brian; Langford, Carol A.; Sindwani, Raj
Background: Granulomatosis with polyangiitis (GPA) (Wegener granulomatosis) frequently presents in the head and neck, and the sinonasal cavity is among the most common areas affected. Although the clinical findings, histologic appearance, and laboratory workup have been described, characteristic findings and the distribution of disease on sinonasal imaging are not well established. The appropriate imaging modality to evaluate for sinonasal involvement is also unclear. Objective: To describe the imaging characteristics, distribution, and location of sinonasal pathology in patients with GPA as noted on computed tomography and magnetic resonance imaging modalities. Methods: A systematic review was conducted of English language articles, by using appropriate search terms, which reported the computed tomography and magnetic resonance imaging findings specific to sinonasal disease in adult subjects with GPA. Studies were included only when they focused primarily on specific imaging results in patients with GPA. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were followed. Results: A total of 50 articles were identified on an initial search of medical literature data bases. There were seven articles that comprised 224 patients who met inclusion criteria. All the articles were retrospective case series and descriptive in nature. A high incidence of patients with GPA who were imaged showed evidence of pathologic findings. The prevalence of key radiographic findings in patients with GPA were the following: mucosal thickening (87.7% of patients), bony destruction (59.9%), and septal erosion (59.4%). There were no randomized or prospective studies that compared imaging findings between patients with GPA and the controls, and no studies that correlated imaging findings with prognosis. Conclusion: Sinus imaging in GPA revealed a spectrum of nonspecific findings. The constellation of septal erosion, mucosal thickening, and bony changes should raise suspicion for GPA. The current literature was insufficient to make any comments on the time course of sinonasal disease and imaging manifestations. Further comparative studies are needed to determine a role for sinonasal imaging in the diagnosis and prognosis of GPA.